BENEFITS OF LEARNING FOREIGN LANGUAGES - Farmonova, Gulchiroy Jamshid qizi; Ochilova , Sabina Utkirovna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
Now, modern world is becoming increasingly globalised and bilingualism. So, learning foreign languages is blossoming year by year. Because communicating with other countries and peoples is incredibly important nowadays. In other words, foreign languages study estimates people’s chances in business, technology, industry, art and government.